Exploring the relationship between personal control and the hospital environment - Williams, Anne; Dawson, Sky; Kristjanson, Linda (Blackwell Publishing, 2008)
Aims & Objectives: This paper describes the further development of the substantive theory Optimising Personal Control to Facilitate Emotional Comfort. In previous work, emotional comfort was identified as a therapeutic state that was influenced by several factors, one of which was the hospital environment. This paper focuses on aspects within the hospital environment that patients perceive to influence their feelings of personal control. Background: A relationship between control and health has been discussed in previous literature. There are indications that aspects of the hospital environment can impact on a patient's perception of control. This project explored personal control in relation to the hospital environment from the perspective of patients.Methods: Grounded theory method was used. Data were collected from patients' interviews and field observations and analysed using the constant comparative method. Interviews were tape-recorded and transcribed verbatim. A qualitative data computer program was used to manage the data. Results: The results confirmed the findings of the original study where hospitalised patients were found to experience feelings of reduced personal control. The conditions of level of security, level of knowing and level of personal value were described in terms of their contribution to the patient's feelings of personal control. Conclusions: Specific directions for further research into the development and evaluation of therapeutic hospital environments that promote personal control and the associated emotional comfort are provided. Relevance to clinical practice: This research highlights the importance of considering patients' feelings of personal control during their hospital stay. Several directions for establishment of therapeutic environments within hospitals are provided, but more research in this area is recommended.